Characterization of NETosis Dynamics in Hypertension and Associated Mechanisms of Renal and Vascular Injury - Landry, Chloé (Université d'Ottawa / University of Ottawa, 2026)
Neutrophil extracellular trap (NET) release is an innate immune process involving chromatin extrusion that has been linked to hypertension and associated vascular and kidney injury. However, reliance on endpoint measurements limits mechanistic insight into NETosis regulation and dynamics. To address this, we developed a live-cell imaging assay and semi-automated, CellProfiler-based analysis pipeline for high-throughput quantification of NETosis progression. This pipeline enables single-cell feature extraction and machine-learning-based classification of NETosis stages, allowing quantitative assessment of stimulus- and dose-dependent NETosis dynamics. The approach was validated in neutrophil-differentiated HL-60 cells and primary mouse bone marrow neutrophils and reliably captured responses to common NETosis inducers and pharmacological inhibitors. We applied this pipeline to an angiotensin II (Ang II)-induced model of hypertension to examine NETosis dynamics across bone marrow and kidney neutrophil compartments. In parallel, the contribution of NETs to renal immune cell recruitment and kidney injury was assessed in Ang II-treated Padi4⁻ᐟ⁻ mice. Although NETs did not accumulate in the kidney and did not contribute to blood pressure elevation or overt kidney injury in this model, temporal single-cell analysis revealed stage-specific alterations in NETosis dynamics in male bone marrow and kidney neutrophils, suggesting altered neutrophil priming originating in the bone marrow that does not translate to tissue injury in this context. Given the established link between NETs and endothelial injury, we next examined the transcriptional response of HUVECs treated with HL-60-derived NETs using bulk RNA sequencing. Pathway and gene set enrichment analyses revealed suppression of G2/M cell cycle regulators alongside upregulation of inflammatory pathways, consistent with activation of a senescence-associated transcriptional program, as supported by Human Universal Senescence Index (hUSI) scoring. Markers of G2/M arrest and senescence were further evaluated in NET-treated HUVECs, with variable support across assays. Together, these findings indicate that NET exposure induces an early senescence-like transcriptional response that precedes, but does not yet manifest as, stable cell cycle exit and bona fide senescence after 24 hours.
Keywords: Neutrophil extracellular traps; High-throughput NET quantification; Hypertension; Kidney injury; Endothelial dysfunction